"Percepción del cuidado humanizado de enfermería y nivel de estrés del paciente hospitalizado en los servicios de medicina. Hospital Regional Docente de Trujillo" - Becerra Castrejón, Fanny Roxana (2015)
This research study, type a descriptive correlational and cross-sectional, was performed in services Regional Medical Teaching Hospital of Trujillo, in order to determine the relationship between perception of humanized nursing care and patient stress level hospitalized. The sample consisted of 46 inpatients who met the inclusion criteria. Perception survey humanized nursing care (EPCHE) and Stress Rating Scale (EVE) analysis of the relationship between the study variables was performed by testing independence: the instruments used for data collection chi-squared criteria (x2); the results were presented in tables simple, double entry .After the analysis reached the following conclusions: 65% of hospitalized patients perceive a humanized regular nursing care, 22% bad, and 13% good; 72% of hospitalized patients have a higher level of stress, 15% have a medium level of stress, and 13% lower; According to the statistical test chi square (X2) is evidence that there is no relationship between variables (p = 0.148).